Quantum photonics on a chip - A. Katiyi; A. Karabchevsky (APL Quantum, 2025)
Optical chips for quantum photonics are cutting-edge technology, merging photonics and quantum mechanics to manipulate light at the quantum level. These chips are crucial for advancing quantum computing, secure communication, and precision sensing by integrating photonic components such as waveguides, beam splitters, and detectors to manipulate single photons, the fundamental carriers of quantum information. Key advancements in optical chips include low-loss waveguides, efficient single-photon sources, and high-fidelity quantum gates, all essential for scalable quantum circuits. Integrating these circuits on a chip offers significant advantages in miniaturization, stability, and reproducibility over traditional bulk optics setups. Recent breakthroughs in materials science and nanofabrication have propelled the field forward, enabling the production of chips with higher precision and lower defect rates. Silicon photonics, in particular, has become a prominent platform due to its compatibility with existing semiconductor manufacturing processes, facilitating the integration of quantum photonic circuits with classical electronic systems. Here, we share our vision of the future of optical chips for quantum photonics, which hold promise for various applications. In quantum computing, they enable the development of compact and scalable quantum processors. In communication, they provide the foundation for ultra-secure quantum networks through quantum key distribution. In sensing, they allow for high-precision measurements that surpass classical limits. As research progresses, optical chips are expected to play a critical role in realizing the full potential of quantum technologies.